Kształcenie nauczycieli dla edukacji włączającej - Jachimczak, Beata (Studia Edukacyjne, 2018)
Inclusive education as idea of education appeared in the 1990s. The main aim of inclusive education is full participation, opposition to exclusion of anyone from the possibility of education together with their peers, in their place of residence. It draws attention to the necessity to change the educational policy. In the inclusive education most important are needs (special needs) and oportunities of students, and support. One of the important conditions for the implementation of the idea is proper preparation of teachers for inclusive education. Analyzes of international experience indicate that there are similar problems in most countries. It is worth to recognize them, to take systemic action as soon as possible leading to the change of unfavorable indicators in Poland.